Pemanfaatan Metode Agile dalam Pengembangan Aplikasi CISEA pada PT. Bukit AsamTbk - Risma Nur Aini; Allsela Meiriza; Dinna Yunika Hardiyanti; Khoirusy Syafaat (Politeknik Harapan Bersama, 2026)
Key Performance Indicator (KPI) management is a crucial aspect in measuring and evaluating organizational performance in a systematic and sustainable manner. However, KPI management processes that are still conducted manually may lead to several issues, such as verification delays, lack of data integration, and low accuracy in performance reporting. This study aims to develop an Electronic Balanced Scorecard (e-BSC) module within the CISEA application to support integrated and digital-based KPI management. The system development method employed in this study is Agile, which consists of planning, design, development, testing, documentation, and deployment stages. During the planning stage, system requirements were analyzed through observations and discussions with relevant stakeholders. The design stage utilized Unified Modeling Language (UML) to model the system, database structure, and user interface. System implementation was carried out using PHP as the programming language and MySQL as the database management system, with the user interface developed using HTML and CSS. System testing was conducted using the black box testing method to ensure that all system functions operated in accordance with user requirements. The results of this study indicate that the developed e-BSC module is capable of facilitating KPI input, verification, approval, and performance reporting processes in a more systematic, integrated and structured manner. Therefore, the system is expected to enhance the quality of organizational performance management and support accurate and timely managerial decision-making.